THE UNCANNY PHENOMENON PORTRAYED IN KATHRYN STOCKETT’S “THE HELP”: POSTCOLONIAL APPROACH - Erlis, Erlis; Putra, Emil Eka (SCIENTIA JOURNAL, 2020)
This research analyzes the uncanny phenomenon in “The Help” by Kathryn Stockett. This research aims to identify uncanny phenomenon anid how it is reflected in the story. This research also uses the uncanny theory by Homi K. Bhabha. The researcher collects the data by reading the novel and writes down the data that is matched with the problem that is going to be identified. After the data has been gathered, the researcher analyzed the data with qualitative descriptive method and the result is presented by words and sentences. The result of the research shoiws thiat uncanny phenomenon occurs iin characters through their conversation and activities. The uncanny phenomenon mostly reflected in the maid’s (colored skin) experiences dealing with their boss (white skin). The experiences classified into the differences in using restroom, utensils, eating etiquette, etc